The safety and efficacy of laparoscopic retrograde appendicectomy, base-to-tip approach - Ko, Ara; Lindsay, Perry; Choi, Julian (Frontiers in Surgery, 2023)
Laparoscopic appendicectomy is one of the most frequently performed surgical procedures worldwide. There is limited evidence evaluating the role and safety of laparoscopic retrograde appendicectomy (LRA), base to tip approach, compared to standard laparoscopic antegrade appendicectomy (LAA), tip to base approach. This study aims to assess the safety of LRA compared to LAA in terms of intra-abdominal collection (IAC) rate and using Sunshine Appendicitis Grading System (SAGS).Records of two-hundred and seventy-three patients undergoing laparoscopic appendicectomy by LAA and LRA approaches were analysed. The severity of appendicitis was rated using a standardised Sunshine Appendicitis Grading System (SAGS) score intraoperatively. The primary outcome measure was the occurrence of an intra-abdominal collection, and secondary measures were procedure time, post-operative length of stay and other complications.Of the two-hundred and seventy-three patients, there were two patients who developed an intra-abdominal collection. Both patients were in the LAA group with SAGS IV scores.Between SAGS IV patients, Chi-squared p value of 0.6691. Therefore, there was no statically significant difference in the intra-abdominal collection (IAC) rate between LAA and LRA groups from this study.The current study has shown that laparoscopic retrograde appendicectomy (LRA) does not increase risk of intra-abdominal collection compared to laparoscopic antegrade appendicectomy (LAA) within the limit of this study.Deleted: Surgeons should consider this approach when faced with retro-caecal, retro-ileal and pelvic appendicitis.